The Financial Health Diaries: What do the Financial and Health Diaries tell us about decisions to renew in health insurance? - Kramer, Berber; Janssens, Wendy (PharmAccess Foundation, 2017)
What influences renewal in insurance? Is it poverty (low wealth) or seasonality in how much cash a household has at hand (liquidity)? These and other questions were investigated in the Financial and Health Diaries study, consisting of weekly interviews with 240 households, over a one-year period. 120 of these households were located in Kwara State, Nigeria. The recorded data shed light on how to improve marketing strategies to target people that are up for renewal in the context of the Kwara State Health Insurance program.